2011
DOI: 10.3748/wjg.v17.i1.89
|View full text |Cite
|
Sign up to set email alerts
|

Impact of diet on long-term decline in gastric cancer incidence in Poland

Abstract: The decline of gastric cancer incidence probably resulted from increased consumption of vegetables, fruit and vitamin C and a decrease in salt consumption.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…32 – 34 The inverse association between fruit intake and cancer incidence, possibly due to the protective effect of increased fiber intake, 30 agreed with previous findings. 19 , 35 The inverse association between alcoholic beverage availability and cancer incidence might be attributable to the protective effect of moderate drinking, 36 although this favorable association has been recently challenged. 37 …”
Section: Discussionmentioning
confidence: 99%
“…32 – 34 The inverse association between fruit intake and cancer incidence, possibly due to the protective effect of increased fiber intake, 30 agreed with previous findings. 19 , 35 The inverse association between alcoholic beverage availability and cancer incidence might be attributable to the protective effect of moderate drinking, 36 although this favorable association has been recently challenged. 37 …”
Section: Discussionmentioning
confidence: 99%
“…FBaS have mainly been used to describe long‐term food availability, and to investigate its local and global drivers. Different studies have used FBaS to assess dietary changes over time , to compare worldwide availability of fats, sugar, starch, n‐3 and n‐6 fatty acids and different food groups , to assess association of food availability with population overweight and obesity and with different morbidities or mortality , and to evaluate adherence to different diets (e.g. the Mediterranean diet) .…”
Section: Overview Of Existing Sources Of Dietary Datamentioning
confidence: 99%
“…In our study, intake of food containing risk factors (pickled vegetables, fermented soy-foods, processed meat 30 g/d or above, and bacon, or salted foods), might be associated with increased GC risk. Recent study has showed that increased consumption of vegetables, fruit and vitamin C and a decrease in salt consumption could result the decline of GC incidence in Poland for about forty years (Jarosz et al, 2011). So in the future, increasing intake of food containing protective factors, and limiting or avoiding intake of food containing risk factors might help to prevent GC.…”
Section: Discussionmentioning
confidence: 99%